Reduced Reflex Autonomic Responses Following Intradetrusor OnabotulinumtoxinA Injections: A Pre-/Post-study in Individuals With Cervical and Upper Thoracic Spinal Cord Injury - Dorey, Tristan W.; Walter, Matthias; Krassioukov, Andrei V. (Frontiers in Physiology, 2021)
Urodynamic studies (UDS) can provoke autonomic dysreflexia (AD) in individuals with spinal cord injury (SCI) at and above the sixth thoracic spinal segment potentially leading to profound vagally mediated heart rate (HR) reductions. In this study (https://clinicaltrials.gov/ct2/show/results/NCT02298660) we test the hypothesis that intradetrusor onabotulinumtoxinA injections will improve HR and its variability (HRV) responses to UDS in individuals with cervical and thoracic SCI. A total of 19 participants with chronic SCI (5 women; mean age 42.5 ± 7.9 years) with confirmed neurogenic detrusor overactivity underwent UDS before (i.e. baseline) and one month after intradetrusor onabotulinumtoxinA (200 U) injections (post-treatment). Continuous electrocardiography and blood pressure (BP) recordings were used to assess RR-interval, time and frequency domain metrics of HRV (a surrogate marker of autonomic nervous system activity), and AD pre- and post-treatment. UDS pre-treatment resulted in increased RR-interval as well as time and frequency domain metrics of HRV. Vagally mediated increases in high frequency (HF) power during UDS were larger in participants with cervical compared to upper thoracic SCI. Post-treatment, UDS had no effect on RR-interval and significantly reduced instances of bradycardia. Furthermore, intradetrusor onabotulinumtoxinA injections significantly reduced time domain metrics of HRV and HF power responses to UDS across all participants. Changes in HRV during UDS could be a potential indicator of improved autonomic cardiovascular function following interventions such as intradetrusor onabotulinumtoxinA injections.